Entre a République e o Reich: as múltiplas temporalidades em Ernest Lavisse - Borges, Rilton Ferreira (2020)
From an analysis of the Essais sur l'Allemagne Impériale, we propose that Ernest Lavisse, an important historian linked to the Methodical School and part of the context of the constitution of history as an autonomous science, already brought some reflections considered proper to the historiography after the emergence of the École des Annales. More accurately, we seek to demonstrate that the notion of multiple temporalities was already considered at the end of the nineteenth century, even though it was not systematized at that time as Fernand Braudel did. The essays on the work we analyzed were written between 1871 and 1887, against the background of the recent French defeat in the Franco-Prussian War. Throughout the essays Lavisse describes and analyzes German characteristics while building a nation identity and ideal for France. Through his reflections, the historian has come to realize in Germany a stage of political development prior to that experienced by France, so that the German Reich represents a past to be overcome, while the French Républic represents a future to be reached